Application of dimensional analysis in systems modeling and control design - Balaguer, Pedro (The Institution of Engineering and Technology, 2013)
This book is about applying dimensional analysis concepts to control theory and control engineering problems. We find two fundamental book objectives: (i) to introduce the fundamentals of dimensional analysis to control engineers and researchers and (ii) to show how to exploit the benefits that dimensional analysis can provide to control theoretic and practical problems.